Kurdish Journalism Language after the Uprising (1991 – 1999) - بكر, همداد حسين (Sulaimani Journal for Humanities, 2001)
This paper aims at studying Kurdish Journalism Language after uprising. Because the uprising led to an over all change in the life of people in Kurdistan. This change is evident in public mass media and journalistic foundtions(establishments) in particular. The Kurdish Journalism Language, through various party and governmental periodicals, more specifically in the fields of politics, social, scientific and sport... has borrowed several new words and terms from forign languages. In addition, several new and terms have been formed for political and scientific phenomenon, which is performed through the language of Journaistic arts such as “news” article, report and advertisement, Furthermore another fact is reproved that language is alive phenomenon which continually changes and is directly related to human race. As far as the scope is concerned, the paper is restricted to Journalism in Iraqi Kurdistan. The paper consists of an introductory section, two chapters, aconclusion and abibliography for consulted references.